Gastric Calcifying Fibrous Tumour. (2006) - Attila, Tan; Chen, Dean; Gardiner, Geoffrey W; Ptak, Theadore W; Marcon, Norman E
Abstract : Intramucosal gastric tumours are most commonly found to be gastrointestinal stromal tumours or leiomyomas (smooth muscle tumours); however, a variety of other uncommon mesenchymal tumours can occur in the stomach wall. A rare benign calcifying fibrous tumour is reported and the endoscopic appearance, ultrasound findings and morphology are documented. A review of the literature found only two similar cases.